2015
DOI: 10.4028/www.scientific.net/msf.827.99
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Optical and Structure Properties of Polydimethylsiloxanes

Abstract: Polydimethylsiloxanes (PDMS), (CH3)3SiO-[Si(CH3)2O]n-Si(CH3)3, known as silicone oil is a tamponade liquid which is very important in vitreoretinal surgery, especially in the treatment of complicated retinal detachment. Here, we investigated the optical properties and structure of silicone oil with high viscosity silicone oil of 5500 cSt and low viscosity silicone oil of 1300 cSt in order to understand the changing of physical properties of silicone oil before and after using in vitreoretinal surgery as a tamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 10 publications
0
16
0
5
Order By: Relevance
“…Several studies have shown that the low viscosity of PDMS has a higher emulsification tendency than other viscosities. This is influenced by low surface tension and impurities [ 3 ]. Both cause ocular toxicity by spreading to the eye tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that the low viscosity of PDMS has a higher emulsification tendency than other viscosities. This is influenced by low surface tension and impurities [ 3 ]. Both cause ocular toxicity by spreading to the eye tissue.…”
Section: Discussionmentioning
confidence: 99%
“…However, PDMS with low viscosity also has a weakness in the form of a higher possibility of emulsification than PDMS with high viscosity [ 1 ]. Impurities are one of the main reasons for emulsification [ 2 , 3 ]. These impurities are thought to cause ocular toxicity by spreading to the surrounding eye tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Previous experiments have been conducted utilizing spectrometers with varying wavelengths and refractive index meters in order to investigate the optical characteristics of SiO in various scenarios, including both used and unused SiO, oils with different viscosities, different durations of intraocular SiO retention, as well as different surgical indications and related procedures. 8,9 Previous research has indicated that eyes containing fresh, non-emulsified SiOs exhibit increased transmittance and decreased reflectance of light within the visible spectrum. Additionally, these eyes demonstrate a higher refractive index.…”
Section: Np112mentioning
confidence: 99%
“…Because SiO does not contain fluorophores that can be stimulated by blue wavelength light, it does not appear hyperautofluorescent. 2,8 The emulsified SiO bubbles appear dark and hypoautofluorescent, effectively blocking the underlying retinal fluorescence.…”
Section: Np112mentioning
confidence: 99%
“…Dalam pengukuran tersebut diperoleh nilai estimasi viskositas yang masih jauh dibandingkan dengan nilai viskositas sebenarnya. Hal ini dikarenakan silicone oil yang dilarutkan pada cairan BSS tidak larut secara sempurna [5]. Untuk itu, pada penelitian ini dilakukan teknik pengukuran melalui metode pengenceran dengan menggunakan variasi pelarut berupa pelarut organik yaitu kloroform dan toluene.…”
Section: Pendahuluanunclassified